2021
DOI: 10.1111/aor.13833
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplant waiting list implications of increased ventricular assist device use as a bridge strategy: A national analysis

Abstract: The previous decade has seen a tremendous increase in both the volume and survival benefit of ventricular assist device (VAD) implantation. 1-3 Though a growing proportion of implantations are intended as destination therapy, about 50% remain part of a bridge strategy, with patients either receiving VADs prior to listing as a bridge to decision (BTD) or after listing as a bridge to transplant (BTT). 4 This rapidly expanding population of VAD patients awaiting HT may face an epidemiological bottleneck as the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Notably, a significant improvement in the overall survival of LVAD patients has been observed since the implementation of the latest generation of fully magnetically levitated platforms, despite a slight decrease in HTx rates of LVAD patients in recent years [ 10 ]. The widespread use of LVAD implantation as a BTT strategy has not only improved the survival rates of patients on the transplant waiting list, but has also enabled candidates to survive long waiting periods [ 11 ]. This phenomenon can be explained by the improvement in heart failure symptoms and clinical condition of BTT patients on LVAD support [ 11 ].…”
Section: The Concept Of Bridge To Transplantation Lvad Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a significant improvement in the overall survival of LVAD patients has been observed since the implementation of the latest generation of fully magnetically levitated platforms, despite a slight decrease in HTx rates of LVAD patients in recent years [ 10 ]. The widespread use of LVAD implantation as a BTT strategy has not only improved the survival rates of patients on the transplant waiting list, but has also enabled candidates to survive long waiting periods [ 11 ]. This phenomenon can be explained by the improvement in heart failure symptoms and clinical condition of BTT patients on LVAD support [ 11 ].…”
Section: The Concept Of Bridge To Transplantation Lvad Therapymentioning
confidence: 99%
“…The widespread use of LVAD implantation as a BTT strategy has not only improved the survival rates of patients on the transplant waiting list, but has also enabled candidates to survive long waiting periods [ 11 ]. This phenomenon can be explained by the improvement in heart failure symptoms and clinical condition of BTT patients on LVAD support [ 11 ]. Despite the increased risk of adverse events (AEs) associated with LVAD support, BTT remains an effective strategy because it reduces the likelihood of death and removal from the waiting list due to clinical deterioration, which is often the only alternative to HTx due to organ shortage [ 11 ] (Fig.…”
Section: The Concept Of Bridge To Transplantation Lvad Therapymentioning
confidence: 99%
“…In contrast, more options are available for graft assessment pre-transplantation for hearts preserved via NMP due to their active metabolic state. Recent research has demonstrated the capability to measure a wide array of functional parameters including vascular function, cardiac oxygen efficiency, levels of high-energy phosphates, and cardiac oxygen consumption in NMP grafts, although none have been implemented in the clinic [ 12 , 13 ]. Similarly, a plethora of ‘conventional’ biomarkers, including candidate predictors of graft inflammation (interleukin 6—IL-6, vascular cell adhesion molecule 1—VCAM-1, P- and E-selectin, tumor necrosis factor‐α—TNF‐α), ischemic/reperfusion injury (TNF‐α), the expression of anti- coagulation factors (thrombomodulin), as well as myocyte injury/cardiomyocyte death (Troponin T), among others can be analyzed from the circulating perfusate [ 14 16 ].…”
Section: Current Assessment Techniquesmentioning
confidence: 99%
“…Presently, around 90% of patients recommended for a MCS device are implanted with left ventricular assist devices (LVADs) 4 . LVADs are now reliable devices to provide lifesaving support to the patient whose treatment is halted due to the scarcity or availability of a distant heart donor 5 . This battery‐operated device is inserted inside a human body and implanted just below the heart (battery and controller remain outside the body).…”
Section: Introductionmentioning
confidence: 99%